SLAOrchestrator: Reducing the Cost of Performance SLAs for Cloud Data Analytics - Ortiz, Jennifer; Lee, Brendan; Balazinska, Magdalena; Gehrke, Johannes; Hellerstein, Joseph L. (2018 [USENIX] Annual Technical Conference, 2018)
SLAOrchestrator is a new system designed to reduce the price increases necessary to support performance SLAs in cloud analytics systems. SLAOrchestrator is designed for SLAs that guarantee per-query execution times. Its core architecture consists of a double learning loop that improves both SLAs and resource management over time. It further utilizes an efficient combination of elastic query scheduling and multi-tenant resource provisioning algorithms to reduce the costs of performance guarantees.